First-generation antipsychotics use and reduced risk of pneumonia—Clinical implications in SARS-CoV2 treatment: A systematic review and meta-analysis of observational studies - Abhirami Eby, Elsa Jacob, P. Samuel Gideon George (Journal of Applied Pharmaceutical Science, 2022)
The use of antipsychotics (AP) has been linked to nearly 60% increase in the incidence of pneumonia. The study purposes to devise safest treatment regimens for psychiatric patients with underlying respiratory comorbidities. A systematic literature search was conducted. A total of 41 studies were evaluated, which included 33 articles for metaanalysis. The quality of retrieved articles was screened by reviewing independently. The risk of bias in each study was assessed using the Newcastle–Ottawa Scale. Inter-rater agreement calculation was performed using Rayyan QCRI. Statistical analysis was performed using R 4.0.3. The meta-analysis conducted revealed that the risk of pneumonia (OR = 1.66; 95% CI = 1.64–1.68) and respiratory failure (OR = 1.79; 95% CI = 1.61–2.00) were higher in psychotropic users compared to nonusers. Pneumonia risk was higher in second-generation antipsychotic users (OR = 1.12; 95% CI = 1.01–1.25) compared to other antipsychotic users. However, no association was found between firstgeneration antipsychotics and pneumonia compared to other psychotropic exposure (OR = 0.93; 95% CI = 0.86–0.99). Chlorpromazine, sulpiride, and aripiprazole were found to be statistically safer compared to other AP. AP should be of appropriate choice in patients with SARS-CoV-2 infection, recurrent pneumonia history or those with opportunistic infections.
Keywords: Psychotropics, antipsychotics, respiratory failure, pneumonia, COVID-19, PRISMA